2012
DOI: 10.1164/rccm.201206-1013oc
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Analysis of Blood Biomarkers in Chronic Obstructive Pulmonary Disease

Abstract: Rationale: A genome-wide association study (GWAS) for circulating chronic obstructive pulmonary disease (COPD) biomarkers could identify genetic determinants of biomarker levels and COPD susceptibility. Objectives: To identify genetic variants of circulating protein biomarkers and novel genetic determinants of COPD. Methods: GWAS was performed for two pneumoproteins, Clara cell secretory protein (CC16) and surfactant protein D (SP-D), and five systemic inflammatory markers (C-reactive protein, fibrinogen, IL-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 53 publications
6
99
0
Order By: Relevance
“…In a recent candidate gene association study by Kim and colleagues, SP-D was identified as one of two risk loci for COPD from among circulating COPD biomarkers measured in the ECLIPSE (Evaluation of COPD Longitudinally to Identify Predictive Surrogate Endpoints) study (104). These findings support the relevance of SP-D in the pathogenesis of COPD.…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 64%
“…In a recent candidate gene association study by Kim and colleagues, SP-D was identified as one of two risk loci for COPD from among circulating COPD biomarkers measured in the ECLIPSE (Evaluation of COPD Longitudinally to Identify Predictive Surrogate Endpoints) study (104). These findings support the relevance of SP-D in the pathogenesis of COPD.…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 64%
“…SPD is mainly produced in type II pneumocytes [96,97] and plays an important role in pulmonary immune defense [98] , making it an interesting potential biomarker in COPD. In this respect, polymorphisms in the surfactant protein-D gene (SFTPD) have been shown to be associated with susceptibility to develop COPD and to influence serum concentrations of SPD [22,77] . Furthermore, SPD levels were found to be elevated in COPD patients when compared to healthy smoking controls, although no association with COPD severity [80] nor with the rate of change in FEV 1 [26] was observed.…”
Section: Prioritized Copd Protein Biomarkersmentioning
confidence: 99%
“…CC-16 is predominantly secreted from non-ciliated club cells and is localized in terminal and respiratory bronchial epithelia [99] . Significant associations between several single nucleotide polymorphisms and circulating levels of CC-16 have been identified in genome-wide association studies, however, no strong associations between genotypic variations, circulating CC16 levels and risk for developing COPD were observed [22] . CC-16 is decreased in COPD patients when compared to healthy smoking controls [78] and has been significantly and independently associated with the rate of change in FEV 1 [26] .…”
Section: Prioritized Copd Protein Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim and colleagues performed a GWAS for 2 pneumoproteins (clara cell secretory protein, CC16, and surfactant protein D, SP-D) as well as 5 inflammatory biomarkers (fibrinogen, C-reactive protein (CRP), interleukin-6 (IL-6), IL-8, and tumor necrosis factor-alpha (TNF-alpha) in the ECLIPSE study. 62 They identified 1 region of association with Clara cell secretory protein (CC16) levels in COPD individuals near the secretoglobin, family 1A, member 1 (uteroglobin) gene, SCGB1A1, which encodes CC16, and another region of association 20 million base pairs away on the same chromosome. SNPs near the surfactant protein D coding gene, SFTPD, were associated with surfactant protein D (SP-D) levels, but SNPs on 2 other chromosomes were significantly associated as well, suggesting that these other chromosomal regions encode trans-acting regulatory factors.…”
Section: Copd-related Phenotype Genomewide Association Studiesmentioning
confidence: 99%